Dampak Kecanduan Media Sosial Terhadap Kesehatan Mental - Putri, Adhisty Bayuningtias; Atmoko, Waluyo Budi (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Mental health is important in human life because it affects the ability to think and act. Declining mental health can interfere with human life. Social media addiction and excessive use of devices can cause a decline mental health. Aims: This research was conducted to predict mental health. Mental health is predicted by depression, anxiety and stress-mediated by fatigue constructs. Decline in mental health is influenced by social media addiction experienced by users. Methods: This research is quantitative research was conducted using a survey design. Data collection used a questionnaire to respondents who use social media more than seven hours per day. The sampling technique used purposive sampling and total sample size 235 respondents . This research was tested using SEM (Structural Equation Modeling) analysis and regression analysis. Results: Based on the analysis, the research results show: fatigue has a significant effect on depression, fatigue has a significant effect on anxiety, fatigue has a significant effect on stress, fatigue mediates the relationship between social media addiction and mental disorders, and social media addiction has a significant effect on fatigue that the five hypotheses proposed are supported. Conclusion: The decline in mental health is caused by the high intensity of social media use mediated by fatigue from using devices for too long.